Diagnosis and management of gastrointestinal neuroendocrine tumors: An evidence-based Canadian consensus. (June 2016) - Singh, Simron; Asa, Sylvia L.; Dey, Chris; Kennecke, Hagen; Laidley, David; Law, Calvin; Asmis, Timothy; Chan, David; Ezzat, Shereen; Goodwin, Rachel; Mete, Ozgur; Pasieka, Janice; et al.
Highlights: Consensus recommendations were developed by a 16-member expert panel. Diagnosis and treatment of GI-NETs is multi-disciplinary. Reassessment throughout the disease course informs ongoing treatment strategy. Effective new therapies should be integrated in clinical practice, as appropriate. Current, evidence-based consensus recommendations improve standards of care. Abstract: The majority of neuroendocrine tumors originate in the digestive system and incidence is increasing within Canada and globally. Due to rapidly evolving evidence related to diagnosis and clinical management, updated guidance on the diagnosis and treatment of gastrointestinal neuroendocrine tumors (GI-NETs) are of clinical importance. Well-differentiated GI-NETs may exhibit indolent clinical behavior and are often metastatic at diagnosis. Some NET patients will develop secretory disease requiring symptom control to optimize quality of life and clinical outcomes. Optimal management of GI-NETs is in a multidisciplinary environment and is multimodal, requiring collaboration between medical, surgical, imaging and pathology specialties. Clinical application of advances in pathological classification and diagnostic technologies, along with evolving surgical, radiotherapeutic and medical therapies are critical to the advancement of patient care. We performed a systematic literature search to update our last set of published guidelines (2010) and identified new level 1 evidence for novel therapies, including telotristat etiprate (TELESTAR), lanreotide (CLARINET), everolimus (RADIANT-2; RADIANT-4) and peptide receptor radionuclide therapy (PRRT; NETTER-1). Integrating these data with the clinical knowledge of 16 multi-disciplinary experts, we devised consensus recommendations to guide state of the art clinical management of GI-NETs.